Counting fuzzy subgroups of symmetric groups S2, S3 and alternating group A4 - Raden Sulaiman ,; Abd Ghafur Ahmad, (Penerbit ukm, 2010)

(untitled)
In this article we compute the number of fuzzy subgroups of symmetric groups S2, S3 and alternating group A4. First, we define an equivalence relation on the set of all fuzzy subgroups of a group G. We represent all of the subgroups of S2, S4 and A4. We use their poset diagrams to determine the number of their fuzzy subgroups